Review of the literature on patient satisfaction with early medical abortion using mifepristone and misoprostol. (July 2011) - Swica, Yael; Raghavan, Sheila; Bracken, Hillary; Dabash, Rasha; Winikoff, Beverly
Early medical abortion with mifepristone and misoprostol is increasingly used by women worldwide. Women report high levels of acceptance and satisfaction with the method, citing privacy, noninvasiveness and ease of use as some of medical abortion''s best features. Improvements in the regimen and in service delivery have resulted in several highly effective options for women that offer new routes of administration of misoprostol, fewer visits to the clinic and shorter procedure times. Further efforts to simplify the method and enhance women''s autonomy could increase satisfaction. In this article, we shall review the key determinants of satisfaction and explore their impact on women''s perceptions of their medical abortion experiences.